2019
DOI: 10.3389/fevo.2019.00281
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Surveys in Silverfish Suggest a Multistep Origin of the Insect Odorant Receptor Gene Family

Abstract: The insect odorant receptor (Or) gene family is among the largest multigene families in insect genomes, but its evolutionary origin and mode of expansion is still a matter of debate. We performed transcriptomic surveys of two wingless insect species, the silverfish Lepisma saccharina and Tricholepidion gertschi, and identified multiple Or gene family members in both species. A phylogenetic analysis suggests that the silverfish Ors do not fall into the clade comprised of more derived flying insect ligand-bindin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 96 publications
3
21
0
Order By: Relevance
“…While OR genes were absent in non-insect hexapods such as springtails, they were found in winged and non-winged insects ( Brand et al 2018). According to a phylogenetic analysis of OR genes there is an intermediate clade of primitive ORs expressed in bristletails, firebrats, or silverfish between GRs and the ORs of flying insects (Thoma et al 2019). These primitive ORs then disappeared in flying insects, e.g., in damselflies and dragonflies.…”
Section: Genetic Basis and Evolutionmentioning
confidence: 99%
See 3 more Smart Citations
“…While OR genes were absent in non-insect hexapods such as springtails, they were found in winged and non-winged insects ( Brand et al 2018). According to a phylogenetic analysis of OR genes there is an intermediate clade of primitive ORs expressed in bristletails, firebrats, or silverfish between GRs and the ORs of flying insects (Thoma et al 2019). These primitive ORs then disappeared in flying insects, e.g., in damselflies and dragonflies.…”
Section: Genetic Basis and Evolutionmentioning
confidence: 99%
“…The current state of knowledge supports the view that the ORs evolved from the GRs in a stepwise process. Starting with primitive ORs in early terrestrial insects (Thoma et al 2019), the olfactory system has expanded its receptor repertoire with the occurrence of Orco proteins in Zygentoma (Brand et al 2018) and ended up with the versatile OR complexes in flying insects (Brand et al 2018;Thoma et al 2019) (Fig. 2c).…”
Section: Genetic Basis and Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Missbach et al (14) suggested that the OR/Orco system represents a specific adaptation associated with insect flight (but see (13) for an opposing view). While OR genes likely evolved in the common ancestor of modern insects, perhaps as an adaptation to terrestrial conditions (13, 25), the OR/Orco system may have arisen more recently (15). Indeed, the fact that genomes of early-diverging (non-flying) insect lineages, such as jumping bristletails (Archaeognatha), have ORs but not Orco, suggests the OR/Orco system has a later origin and facilitates rapid olfaction in winged insects (15).…”
Section: Resultsmentioning
confidence: 99%